Pertumbuhan ikan Papuyu (Anabas testudineus Bloch) dengan pemberian ekstrak Ubi Jalar Ungu ( Ipomea batatas L) sebagai sumber probiotik pada pakan komersial - Sri Herlina (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2018)
This study aims to determine the growth of Papuyu fish (Anabas testudineus Bloch) with the provision of purple sweet potato extract as a source of prebiotics of commercial feed. The study used Completely Randomized Design (RAL) consisting of 4 treatments with 3 replicates, namely: Treatment A: feeding with the addition of prebiotics of 1 ml/kg of feed, Treatment B: Feeding with the addition of prebiotics of 2 ml/kg of feed, Treatment C: Feeding with prebiotic addition of 3 ml/kg of feed and D (Control). Parameters observed included relative weight growth, survival rate and water quality. The results showed that purple sweet potato extract did not significantly affect the relative growth of Papuyu fish. The highest growth was in C treatment (272.42%) and the lowest was on treatment D (93.07%). The survival of fish during the study was 100%.